2015
DOI: 10.2135/cropsci2014.03.0194
|View full text |Cite
|
Sign up to set email alerts
|

Pollen‐mediated Gene Flow in Camelina sativa (L.) Crantz

Abstract: Camelina sativa (L.) Crantz is a biofuel crop with application on the Great Western Plains of North America that is being developed using genetic engineering. Before release of genetically engineered cultivars, the potential for pollen‐mediated gene flow (PMGF) needs to be assessed to determine if they can coexist with conventional cultivars without causing market harm. Medium‐scale field experiments (40‐m diameter) were conducted in 2011 and 2012 to quantify PMGF using a seed‐expressed florescent marker and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…Camelina sativa (camelina) is mainly self-pollinating, with outcrossing rates of less than 1% ( Walsh et al, 2006 ; Walsh et al, 2015 ). In the study, we used a local landrace that was not a fixed variety.…”
Section: Methodsmentioning
confidence: 99%
“…Camelina sativa (camelina) is mainly self-pollinating, with outcrossing rates of less than 1% ( Walsh et al, 2006 ; Walsh et al, 2015 ). In the study, we used a local landrace that was not a fixed variety.…”
Section: Methodsmentioning
confidence: 99%
“…All results were compared to an alpha value of 0.05. Previous research suggests the relationship between Amaranthus tuberculatus pollen dispersal and distance follows an exponential decay pattern (Liu et al, 2012;Sarangi et al, 2017), and this pattern also has been observed in other wind-pollinated herbaceous species (Walsh et al, 2015;Dong et al, 2016;Chang et al, 2018). Although pollen dispersal has not been examined in Solanum lycopersicum, Beckie and Hall (2008) observed that studies modeling the effect of distance from the pollen donor on pollen dispersal in crop plants (e.g., maize, wheat) generally fit exponential decay or inverse power curves to the relationship.…”
Section: Statistical Analysesmentioning
confidence: 82%
“…Field experiments were conducted using a modified Nelder wheel design 17 , 78 , 79 with the pollen source (GR giant ragweed) planted in the center and the pollen receptors (GS giant ragweed) planted around the center. The experimental area was 80 m × 80 m with a central circle of 80 sq m (10 m diameter) for the pollen-donor block (Fig.…”
Section: Methodsmentioning
confidence: 99%